2021
DOI: 10.1021/acsomega.0c06277
|View full text |Cite
|
Sign up to set email alerts
|

Computational Fluid Dynamics Simulation of Hydrodynamics in a Two-Stage Internal Loop Airlift Reactor with Contraction-Expansion Guide Vane

Abstract: Global circulation and liquid back mixing adversely affect the continuous production of a multistage internal airlift loop reactor. A contraction-expansion guide vane (CEGV) is proposed and combined with a two-stage internal loop airlift reactor (TSILALR) to suppress the liquid back mixing between stages. A computational fluid dynamics (CFD) simulation is conducted to evaluate the performance of the CEGV in the TSILALR. The bubble size distribution and turbulent flow properties in the TSILALR are considered in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 62 publications
2
4
0
Order By: Relevance
“…Segmenting the draft tube could significantly increase the gas holdup in the downcomer. This conclusion is also consistent with relevant research [15].…”
Section: Gas Holdupsupporting
confidence: 93%
See 2 more Smart Citations
“…Segmenting the draft tube could significantly increase the gas holdup in the downcomer. This conclusion is also consistent with relevant research [15].…”
Section: Gas Holdupsupporting
confidence: 93%
“…This study provided valuable insights for optimizing the structure of two-stage ILAR through CFD simulation, which is helpful in developing more efficient bioreactors. To inhibit liquid back mixing between the stages of a twostage ILAR, Shi et al [15] proposed a contraction-expansion guide vane. CFD simulation and experimental results showed that the internals generated local circulation flows at each stage rather than overall circulation flow, which increased the overall gas holdup by 1.98 times.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was confirmed that the gas holdup and k L a increased in the ILALRs with HFPs. Shi et al 41 attempted to suppress the liquid back-mixing in a two-stage ILALR by installing a contraction−expansion guide baffle between the first and second stages. It was found that local circulations in the first and second stages were generated, and local gas holdup increased as compared to a regular twostage ILALR.…”
Section: Introductionmentioning
confidence: 99%
“…The internal components of the airlift loop reactor can improve the transfer performance. Shi et al [17] studied hydrodynamics in a two-stage internal loop airlift reactor with contraction-expansion guide vane. The two-stage had better performance improvement.…”
Section: Introductionmentioning
confidence: 99%